STUDI TENTANG GAMBARAN HISTOLOGI LIMFA DAN JANTUNG MENCIT (Mus musculus) TOKSOPLASMOSIS YANG DITERAPI DENGAN INTERTRIM® LA DAN TOXOPLASMANUUR - , FITRIA EKA KURNIAWATI, drh. Dwi Priyowidodo, MP. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Toxoplasmosis is a disease caused by T.gondii. The study was aimed to determine the effect of Intertrim®LA and Toxoplasmanuur treated in mice infected with T.gondii takizoit. The parameters used were histology lien and cardiac so that this research result can be used as an alternative treatment of toxoplasmosis. The study used 22 female mice were 2 months old and weight about 25-30 grams. Mice were devided into 4 groups. Group I (control without infection), groups II (control infection with T.gondii) 4 mice for each group, group III (infected with T. gondii and Toxoplasmanuur), and group IV (infected with T.gondii and Intertrim®LA) 7 mice for each group. The mice infected by T. gondi takizoit 1x103 intraperitoneally at day 1. Treatment of mice performed on day 2 with 0,2 ml Intertrim®LA once a day and 0,4 ml Toxoplasmanuur twice a day or 8 mg/kg body weight. Lien and cardiac organ taken at necropsy after the mice died. The making of histology preparate were conducted by the Microanatomy Laboratory and the histology examination performedby the Laboratory of General Pathology Laboratory, Veterinary Medicine Faculty, Gadjah Mada University. Data were analyzed descriptive. The results showed that the mice treated by Toxoplasmanuur had clinical symptoms of anorexia, clustered, inactive and deaths occurred on day 4, 5 and 6 as well as by histological examination organ changes. The mice treated by Intertrim®LA died on day 21 by euthanized, the mice did not show clinical symptoms of illness as well as the examination of the organ showed no change. According to the research result, it can be conclude that the use of drugs Intertrim®